2015
DOI: 10.1063/1.4906843
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic tunnel junctions using Co/Ni multilayer electrodes with perpendicular magnetic anisotropy

Abstract: Équipe 101 : Nanomagnétisme et électronique de spinInternational audienceMagnetic and magneto-transport properties of amorphous Al2O3-based magnetic tunnel junctions (MTJ) having two Co/Ni multilayer electrodes exhibiting perpendicular magnetic anisotropy (PMA) are presented. An additional Co/Pt multilayer is required to maintain PMA in the top Co/Ni electrode. Slight stacking variations lead to dramatic magnetic changes due to dipolar interactions between the top and bottom electrodes. Tunnel magneto-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[1][2][3] Among these multilayers, because of their allferromagnetic nature and controllable magnetic anisotropy, Co=Ni multilayers are ideal magnetic electrode materials in spin-valve or magnetic tunnel junctions (MTJs). [4][5][6] Theoretical 7) and experimental studies 8) have shown that magnetic devices with PMA in both the reference and free layers are advantageous for achieving a low spin-transfer torque (STT) switching current and high thermal stability, which are the most pressing issues for the realization of high-density, highspeed STT-MRAMs. STT can also be used to drive domain walls in magnetic nanowires for novel storage applications such as magnetic shift register memory.…”
mentioning
confidence: 99%
“…[1][2][3] Among these multilayers, because of their allferromagnetic nature and controllable magnetic anisotropy, Co=Ni multilayers are ideal magnetic electrode materials in spin-valve or magnetic tunnel junctions (MTJs). [4][5][6] Theoretical 7) and experimental studies 8) have shown that magnetic devices with PMA in both the reference and free layers are advantageous for achieving a low spin-transfer torque (STT) switching current and high thermal stability, which are the most pressing issues for the realization of high-density, highspeed STT-MRAMs. STT can also be used to drive domain walls in magnetic nanowires for novel storage applications such as magnetic shift register memory.…”
mentioning
confidence: 99%
“…Besides, [Co/Ni] has been researched as alternative PMA material and has been employed in p-MTJ because of its high spin polarization and low Gilbert damping constant [8][9][10][11] . Also, [Co/Ni] has been incorporated in an ultrathin SAF [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Among different modern preparation methods of thin-film structures, the alternate and co-deposition of ferromagnetic and nonmagnetic materials can be distinguished. At this, various methods like thermal evaporation, electron beam or magnetron deposition, laser lithography can be used [1][2][3][4]. Regardless of the chosen method, the physical properties of nanostructures will depend on technological conditions: a base pressure in a vacuum chamber, the composition of the residual atmosphere, type and temperature of a substrate, deposition rate, and so on.…”
Section: Introductionmentioning
confidence: 99%